The Influence of Budgeting, Human Resources, and Leadership on Transparency and Accountability in Village Fund Management with Community Participation as a Moderating Variable - Susanti, Novriani; Hizazi, Achmad; Mukhzarudfa, Mukhzarudfa; Arum, Enggar Diah Puspa (PT. Anagata Sembagi Education, 2026)
This research is motivated by the importance of transparency and accountability in Village Fund management as key indicators of village governance success. Although Village Fund allocations have continuously increased, various problems remain in management practices, particularly regarding low transparency and accountability. This study aims to analyze the influence of budgeting, human resources (HRM), and leadership on transparency and accountability in Village Fund management, with community participation as a moderating variable. A quantitative approach with explanatory research design was employed, using primary data collected through structured questionnaires. The analytical technique used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results show that budgeting, HRM, and leadership have a positive and significant influence on both transparency and accountability. Furthermore, community participation is proven to significantly strengthen these relationships. These findings indicate that good Village Fund governance is not only influenced by internal factors of the village government, but also by the active involvement of the community. Thus, improving the quality of budgeting, HRM capacity, leadership, and community participation are key to achieving optimal transparency and accountability in Village Fund management.